Slovakia: Conflict With EU Law (?), Multiple Crises and a Recovery and Resilience Plan - Štrkolec, Miroslav; Vartašová, Anna (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
In this chapter, the state aid policy and rules in Slovakia are discussed, first, by defining the basic legal framework of state aid and the distinction it draws between direct and indirect aid. Second, case laws of the Court of Justice of the EU in this area that have had a significant impact on the policy, legal framework, and the case law of the Slovak courts are also examined (e.g. Frucona case and NCHZ case). A significant part of the chapter is devoted to state aid in times of crisis, such as in the context of the COVID-19 pandemic and the armed conflict in Ukraine. Further, the relationship between the Recovery and Resilience Facility and state aid rules are also discussed. Finally, the chapter concludes with an overview of fiscal measures as a form of indirect state aid. Regardless of the state of crisis, these are an immanent part of the measures that can be considered as state aid. Keywords: state aid, minimum aid, State aid in the times of crisis, Recovery and Resilience Plan, fiscal measures